Nanoparticles as Additives for the Development of High Performance and Environmentally Friendly Engine Lubricants - Fabrice Dassenoy (Japanese Society of Tribologists, 2019)
There has been growing interest in nanoparticles for tribological applications over the past 20 years. Studies have shown their remarkable lubricating properties, namely friction-reduction and anti-wear, especially when used as lubricant additives. This makes them potential candidates for replacing the additives currently used in automobile lubricants, known to be pollutants and less efficient in certain specific conditions. Among the nanoparticles with proven tribological performance are carbon nanoparticles (nanotubes, onion, diamond, etc.), BN and TiO2 nanoparticles, and Inorganic Fullerene-like (IF) metal disulfides (IF-MoS2, IF-WS2). At the Laboratory of Tribology and Dynamic of Systems (LTDS) of the Ecole Centrale of Lyon (ECL), these nanoparticles have been the subject of detailed investigation for more than fifteen years. Many key issues have been tackled, such as the conditions leading to these properties, the lubrication mechanisms involved, and the influence of parameters such as the size, the structure, and the morphology of the nanoparticles on both their tribological properties and lubrication mechanisms. In order to answer such questions, state-of-the-art characterization techniques are required, often in situ, and sometimes extremely complex to set up. Some of them can even visualize the behavior of a nanoparticle in real time while it is undergoing tribological testing. Researchers now have good understanding of the way these nanoparticles behave, and are able to identify the key parameters to be adjusted to optimize their lubrication properties. In this article, the performance of nanoparticles when used as additives will be described, with particular attention given to metal disulfide nanoparticles. Furthermore, the influence of key parameters on the performance of oils containing nanoparticles will be discussed and the lubrication mechanisms of the metal disulfide nanoparticles will be presented in detail. The issues remaining to be solved before developing new lubricants containing nanoparticles will be also discussed. Finally, we show how fully formulated lubricants containing nanoparticles behave when tested under conditions close to the final application (automotive engine and gearboxes).